2017
DOI: 10.3892/ol.2017.7665
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS contribute to oridonin-induced HepG2 apoptosis through PARP activation

Abstract: Oridonin, the main active constituent of Rabdosia rubescens, is known to exert antitumor activity via the induction of apoptosis in numerous types of human cancer cells. However, the underlying regulatory mechanisms of mitochondrial ROS in oridonin-induced HepG2 apoptosis remain largely unknown, due to limitations of subcellular imaging resolution. Previously, it has been suggested that mitochondria serve a potential role in sensing and signaling cellular redox changes in vital biological processes such as cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…As a high concentration of oridonin was reported to induce apoptosis, therefore, to investigate whether lower concentrations of oridonin could induce apoptosis in H1688 cells, some experiments were performed. First, as demonstrated in Figure 2A, the result of Hoechst staining showed that the percentage of apoptotic cells characterized by nuclear condensation and fragmentation was approximately 4.88 ± 1.22% in the control group (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…As a high concentration of oridonin was reported to induce apoptosis, therefore, to investigate whether lower concentrations of oridonin could induce apoptosis in H1688 cells, some experiments were performed. First, as demonstrated in Figure 2A, the result of Hoechst staining showed that the percentage of apoptotic cells characterized by nuclear condensation and fragmentation was approximately 4.88 ± 1.22% in the control group (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Oridonin inhibits cell growth and induces apoptosis through ER stress and ASK1/JNK signaling pathways in human hepatocellular carcinoma Huh6 cells [559]. Besides, the mitochondrial redox change is proved to be a potential mediator for the pro-apoptosis effect of oridonin [565]. The anti-proliferative effect of oridonin is also shown to be associated with mitochondrial-mediated apoptosis, which is characterized by mitochondrial membrane potential reduction, subsequent cytochrome c release, PARP, caspase-3 and -9 activation, and decreased Bcl-2/Bax ratio [551,565,574,575].…”
Section: Oridoninmentioning
confidence: 99%
“…Oridonin induces apoptosis in human hepatocellular carcinoma HepG2 and Huh6, oral squamous cell carcinoma WSU-HN4, WSU-HN6 and CAL27, and laryngeal cancer HEp-2 cells [550,559,561,565]. It also induces G2/M cell cycle arrest in human oral squamous cell carcinoma WSU-HN4, WSU-HN6 and CAL27, gastric cancer SGC-7901, prostate cancer PC-3 and DU-145, and breast cancer MCF-7 cells [555,561,566,567].…”
Section: Oridoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Oridonin, an active diterpenoid compound extracted and purified from Rabdosia rubescens, has great effects on suppressing the proliferation of esophageal, gastric, liver, and colon cancer cells (6)(7)(8). Previous shreds of evidence have shown that oridonin-mediated apoptosis involves multiple proteins and pathways, such as protein kinase B (AKT), the nuclear factor-kappa B (NF-κB) and mitochondrial redox signaling pathway (9)(10)(11). However, the molecular target of the anti-tumor effect of oridonin has not been fully elucidated, which limits the further clinical application of oridonin.…”
Section: Introductionmentioning
confidence: 99%